(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Whole-body computed tomography (WBCT) can be challenging in identifying extremity injuries due to variations in pain tolerance, other injuries, and examination quality. It is advised to conduct a clinical examination and image review after the patient has stabilized or regained consciousness. Although prompt treatment of limb fractures is crucial, WBCT poses challenges, including incorrect positioning, artifacts, and accurate thin-section computed tomography interpretation. Hand and wrist reconstruction can be complicated, especially when multiple injuries are present. This study aimed to analyze the composition of hand bone fractures in the Kyrgyz Republic and evaluate the effectiveness of cord osteosynthesis compared with alternative procedures for fixing hand bones. Materials and Methods: This retrospective study analyzed data from patients at the National Hospital of the Ministry of Health’s Hand Microsurgery Department in the Kyrgyz Republic from 2018 to 2023. The inclusion criteria were patients aged 18–65 with a confirmed wrist fracture diagnosis, informed consent, and no significant health issues. The 90 patients who underwent cord osteosynthesis comprised Group 1, while Group 2, consisting of 34 patients, underwent standard osteosynthesis. Results: The study found that the mean age of patients in Group 1 was 23.3 ± 1.8 years, while Group 2 had a mean age of 34.3 ± 3.0 years. The mean hospital stay for patients in Group 1 was 6.11 days, while patients in Group 2 had a mean hospital stay of 10.35 days. The mean systolic blood pressure in Group 1 was 108.2 ± 1.4 mmHg, while in Group 2, the mean systolic BP was 115.5 ± 2.4 mmHg. The difference between the two groups was statistically significant (P = 0.009). Conclusion: The findings suggest that cord osteosynthesis may be more effective in treating hand bone fractures than the standard approach.